Komunikasi Persuasif Dalam Film Dokumenter In The Name Of God: A Holy Betrayal Episode 1-3 Kisah Jeong Myeong Seok Melalui Pendekatan Semiotika Charles Sanders Peirce - Fransisca Aquilorum Teme; Mikhael Rajamuda Bataona; Fransiska Desiana Setyaningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
The concepts used in this research are persuasive communication, film and semiotics. This type of research is descriptive qualitative and uses Charles Sanders Peirce’s semiotic analysis method. The data collection techniques used are observation and documentation studies.The results of this research are that there is meaning in the persuasive communication carried out by Jeong Myeong Seok through the persuasive techniques used, namely dissonance/cognitive dissonance techniques, he influences followers to carry out attacks, association techniques, through the message that the mother willThis life and reality is true, the integration/empathy technique where he uses dialogue language to check the victim that he was assigned by God, the reward/payoff idea technique which he does with a promise, the Fear Arrousing technique, he uses threat techniques to attractthe hearts of the victims, the arrangement technique, this technique he uses to attract the attention and support of his followers and finally the red-hearing technique The conclusion of research on the documentary film In The Name Of God: A Holy Betrayal, the story of Jeong Myeong Seok through Charles Sanders Peirce’s approach from these three episodes, found that there was persuasive communication with the dialogue signs used by Jeong Myeong Seok and throughpersuasive communication contains misdirection in its teachings.